Atmospheric Modeling of 137Cs Plumes From the Fukushima Daiichi Nuclear Power Plant—Evaluation of the Model Intercomparison Data of the Science Council of Japan. Issue 14 (28th July 2018) - Kitayama, K.; Morino, Y.; Takigawa, M.; Nakajima, T.; Hayami, H.; Nagai, H.; Terada, H.; Saito, K.; Shimbori, T.; Kajino, M.; Sekiyama, T. T.; Didier, D.; et al.
Abstract: Since the Fukushima Daiichi Nuclear Power Plant (FDNPP) accident in March 2011, atmospheric simulation models have improved our understanding of the atmospheric behavior of radionuclides. Model intercomparisons provide valuable and useful information for evaluating the validity and variability of individual model results. In this study, we compared results of seven atmospheric transport models used to simulate 137 Cs released from the FDNPP to the atmosphere. All model results used in this analysis had been submitted for a model intercomparison project of the Science Council of Japan (2014, http://www.scj.go.jp/en/report/index .html). Here we assessed model performance by comparing model results with observed hourly atmospheric concentrations of 137 Cs, with a particular focus on nine plumes over the Tohoku and Kanto regions. The intercomparison results showed that model performance in reproducing 137 Cs concentrations was highly variable among different models and plumes. In general, models better reproduced plumes that passed over many observation stations. The performance among the models was consistent with the simulated wind fields and the source terms used. We also assessed model performance in relation to accumulated 137 Cs deposition. Simulated areas of high 137 Cs deposition were consistent with the simulated 137 Cs plume pathways, though the models that best simulated atmospheric 137 Cs concentrations were different from those that best simulated deposition. The ensemble mean of all models consistently reproduced atmospheric 137 Cs concentrations and deposition well, suggesting that use of a multimodel ensemble results in more effective and consistent model performance. Key Points: An intercomparison of seven simulation models for atmospheric 137 Cs concentration and deposition was performed Model performance in reproducing observed 137 Cs concentrations in air was highly variable among different models and plumes The multimodel ensemble showed the best model performance and consistency in reproducing 137 Cs concentrations and deposition